Literasi dan Pendampingan Skrining Kesehatan Sistem Pernafasan Dalam Upaya Meningkatkan Program Gerakan Masyarakat Sehat - Zuriati; Nani Asna Dewi; Erika Lubis; Mustika Pramestiyani; Sondang Manurung (J.Abdimas: Community Health, 2021)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease caused by the mycobacterium tuberculosis bacteria and attacks the lung organs. The World Health Organization (WHO) reports that Indonesia is in the third position of the highest TB cases in the world and is a country that contributes 60% of all TB cases in the world. One of the efforts to reduce TB cases is through good literacy in the health sector, especially in the respiratory system. Currently, nurses are trying to educate the public with independent health screening in the community. Health care the spearhead in caring for patients, health workers are the front liners who serve the community, especially during the COVID-19 pandemic so that they provide assistance and health screening to the respiratory system which is in line with the efforts of the Healthy Community Movement program. The method used in this activity was direct lectures followed by 15 members of the Kampung Cililitan cadre. The results showed that knowledge of cadres with good criteria increased from 15.3% to 90.6%. The activities of literacy and respiratory system health screening assistance increase cadres' knowledge in order to improve the Healthy Community Movement program.